2014
DOI: 10.1161/circimaging.113.001158
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Hyperemic Myocardial Blood Flow Is Associated With Inducibility of Ventricular Arrhythmia in Ischemic Cardiomyopathy

Abstract: O]H 2 O positron-emission tomography was performed to quantify resting MBF, hyperemic MBF, and coronary flow reserve. Left ventricular dimensions, function, and scar burden were assessed with cardiovascular magnetic resonance imaging. An electrophysiological study was performed to test VA inducibility. Positive electrophysiological study patients (n=12) showed reduced hyperemic MBF (1.25±0.30 versus 1.66±0.38 mL•min ; P<0.01) and coronary flow reserve (1.59±0.49 versus 2.12±0.48; P<0.01) compared with electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 58 publications
(70 reference statements)
1
19
0
Order By: Relevance
“…In patients with ischemic cardiomyopathy, Rijnierse et al found that impaired hyperemic MBF predicted patients who are likely to have inducible VT with programmed electrical stimulation. 17 While both studies are similar in that they showed a relationship between stress MBF and ventricular arrhythmias, the endpoint in the current study was spontaneous ventricular arrhythmia noted on ICD diagnostics, in contrast to inducible arrhythmias in the other study.…”
mentioning
confidence: 46%
“…In patients with ischemic cardiomyopathy, Rijnierse et al found that impaired hyperemic MBF predicted patients who are likely to have inducible VT with programmed electrical stimulation. 17 While both studies are similar in that they showed a relationship between stress MBF and ventricular arrhythmias, the endpoint in the current study was spontaneous ventricular arrhythmia noted on ICD diagnostics, in contrast to inducible arrhythmias in the other study.…”
mentioning
confidence: 46%
“…CMR studies and image analyses were performed as described previously 15. In short, a clinical 1.5-T MRI scanner (Magnetom Avanto; Siemens, Erlangen, Germany) was used with a dedicated phased-array body coil.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, denervated yet viable myocardium may in particular be prone to VA 12 13. Moreover, residual ischaemia even after revascularisation may serve as an important arrhythmic substrate 14 15. Some of these different approaches to evaluate the arrhythmic substrates are, however, intertwined and may actually represent similar pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…44 Coronary perfusion abnormalities generate electrical instability of the myocardium and as a predisposing factor for rhythm disturbances this may be an important prognostic factor concerning postoperative morbidity and mortality. These results are hypothesis-generating for a potential role of quantitative PET perfusion imaging in the risk stratification for arrhythmias in patients with morphologic systemic RV.…”
mentioning
confidence: 99%
“…These results are hypothesis-generating for a potential role of quantitative PET perfusion imaging in the risk stratification for arrhythmias in patients with morphologic systemic RV. 44 …”
mentioning
confidence: 99%